Non-operative treatment of acute appendicitis in children: clinical efficacy of amoxicillin-clavulanic acid in a retrospective single-centre study - Olivier Abbo; Damien Dubois; Clémence Picard; Caroline Munzer; Lucas Ricco; Cécile Lemoine; Isabelle Claudet; Camille Bréhin (BMJ Publishing Group, 2023)
Background The success rate of non-operative treatment (NOT) of acute uncomplicated appendicitis (AUA) in children varies from 65% to 95%. There are no recommendations on the appropriate antibiotic therapy.Objective To determine the clinical efficacy of amoxicillin-clavulanic acid for NOT of AUA in children.Methods Design: Cross-sectional study in a single medical centre. Settings: Emergency department and Paediatric Visceral Surgery department of the Children Hospital in Toulouse, France. Patients: Patients 5-15 years old who were diagnosed with appendicitis, (1) With abdominal pain and a first episode of acute appendicitis, (2) With no radiological or ultrasound evidence of appendicolith, appendiceal perforation, pelvic abscess nor peritonitis, and (3) With non-septic general aspect, were included. Interventions: NOT consisted of hospital admission. The antibiotic treatment was a combination of amoxicillin and clavulanic acid (80 mg/kg/day of amoxicillin): intravenous regimen during 48 hours followed by oral route during 7 days. Main outcome measure: Success rate of amoxicillin-clavulanic acid NOT in children with AUA at 2 years.Results The initial success rate of amoxicillin-clavulanic acid NOT in children with AUA was 100% (104/104 patients). The success rate at 2 years was 85.6% (89/104) at discharge. None of the 15 patients who underwent surgery after recurrence of appendicitis presented with peritonitis, appendiceal perforation nor pelvic abscess.Conclusion Narrowed antibiotic therapy with amoxicillin and clavulanic acid seems to be an alternative to surgery in children with AUA. It is necessary to wait for the results of ongoing studies to confirm these results.